KONSEP KENEGARAAN DAN SUMBER HUKUM : (TELAAH KRITIS ATAS PANDANGAN SAYYID QUṬB DALAM TAFSĪR FĪ ẒILĀL AL-QUR’ĀN) - Nur Fauziyah; M. Aly Haedar (STAI AL-ANWAR SARANG, 2016)
The debate on whether Islam as a religion should merge with state is intriguing and seems to never end. One of the prominent Muslim thinkers who was concerned with this issue is Sayyid Qutb (1906-1966), the author of FÄ« áº’Ä«lÄl alQur'Än, a tafsir work which dominantly colors several Islamic movements such as the Ikhwanul Muslimin. This article describes Qutbâ€™s thought on the state and its legal sources elaborated in the mentioned book. It also traces the historical roots of his thought.Keywords: Sayyid Quá¹b, Islamic State, Ikhwanul Muslimin, tafsir FÄ« áº’Ä«lÄl al-Qur'Än.